2019
DOI: 10.1021/acs.langmuir.9b02046
|View full text |Cite
|
Sign up to set email alerts
|

Self-Sustained Coalescence–Breakup Cycles of Ferrodrops under a Magnetic Field

Abstract: The self-sustained coalescence–breakup cycles of ferrodrops were investigated for the first time by a high-speed camera under various magnetic fields. Under an axial magnetic field, the upper ferrodrop would deform into a conic shape before coalescing with the bottom ferropeak. Within 0.2 ms after coalescence, the minimum width of the expanding neck obeys a power-law relationship with time, while the exponents increase with the magnetic field and deviate with a decreasing trend in the later coalescence. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Utilizing the magnetic force to precisely control the ferrofluid droplet formation and breakup in microfluidics has been widely studied in the past decade. Tan et al studied the formation process of a ferrofluid droplet in a T-junction under the effect of a permanent magnet. They demonstrated that if the magnet was placed downstream of the T-junction, the diameter of the droplet would be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing the magnetic force to precisely control the ferrofluid droplet formation and breakup in microfluidics has been widely studied in the past decade. Tan et al studied the formation process of a ferrofluid droplet in a T-junction under the effect of a permanent magnet. They demonstrated that if the magnet was placed downstream of the T-junction, the diameter of the droplet would be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…A proper pulsation ω 0 = σ ρ V can be deduced for this oscillator and related to a frequency ω 0 = 2π f . Both the oscillating frequency f and the magnetic flux density B were conversely correlated to the representative volume of the ferrodrop by means of an exponential function: f = 0.58 – 0.61 exp(–0.004 B ) . The oscillating frequency increases exponentially with the magnetic flux density, and the maximum coalescing width would exhibit an exponential decrease with the magnetic flux density: a faster oscillation does not give a sufficient time for the expansion of the coalescing width W .…”
Section: Resultsmentioning
confidence: 99%
“…By adjusting the fine-tuning platform, the magnetic flux density exerted on the ferrofluid becomes stronger when the magnet moves vertically upward toward the nozzle. The variation of the magnetic field B in the vertical direction z from the top surface of the magnet was reported in our previous study . The ferrofluid would be divided into more ferrofluid peaks; thus, the volume of each peak decreases and the height becomes lower.…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations